The complete mitochondrial genome of a stonefly species, Peltoperlopsis cebuano (Plecoptera: Peltoperlidae). Issue 1 (2nd January 2019) - Cao, Jinjun; Li, Weihai; Yan, Fengming; Wang, Ying
Abstract: The complete mitochondrial genome of P. cebuano is 15, 790 bp in size and consists of 13 protein-coding genes (PCGs), the large and small ribosomal RNA genes, 22 transfer RNA (tRNA) genes, and a control region. The nucleotide composition is significantly AT biased with an A + T content of 69.4%. Ten PCGs are initiated by ATN codons, except ND1, ND2, and ND5 start with TTG, GTG, and GTG. Twelve PCGs use the typical stop codon TAA/TAG, whereas the remaining COII gene terminated with a single T. Our phylogenetic result showed that P. cebuano was closely related to Cryptoperla stilifera and the relationship among three families was Pteronarcyidae + (Peltoperlidae + Styloperlidae). This result supports the traditional morphology-based classification and our previously phylogenetic result.